1984
DOI: 10.1177/003693308402900204
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypersensitivity in the Alginate Industry

Abstract: Salts of alginic acid are complex polymerised polysaccharides which are chemically extracted from seaweed. Workers in the alginate industry are exposed to dust from dried milled seaweed and pure alginate compounds. In this survey of one of the two factories in Britain producing alginates, we found evidence of pulmonary hypersensitivity to seaweed dust in seven per cent of the total work force, and evidence of precipitating antibody to sodium alginate and seaweed extracts in the serum of 4.5 per cent of the wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…A fatal case of anaphylaxis caused by alginate paste used for dental impressions, and a single report of anaphylaxis caused by sodium alginate contained in Gaviscon for the management of dyspepsia, have also been reported . Furthermore, occupational pulmonary hypersensitivity to alginates was noted in 7% of workers exposed to dried milled seaweed and alginate compounds . We report the first case of anaphylaxis caused by a calcium sodium alginate dressing.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A fatal case of anaphylaxis caused by alginate paste used for dental impressions, and a single report of anaphylaxis caused by sodium alginate contained in Gaviscon for the management of dyspepsia, have also been reported . Furthermore, occupational pulmonary hypersensitivity to alginates was noted in 7% of workers exposed to dried milled seaweed and alginate compounds . We report the first case of anaphylaxis caused by a calcium sodium alginate dressing.…”
Section: Discussionmentioning
confidence: 85%
“…2,3 Furthermore, occupational pulmonary hypersensitivity to alginates was noted in 7% of workers exposed to dried milled seaweed and alginate compounds. 4 We report the first case of anaphylaxis caused by a calcium sodium alginate dressing.…”
mentioning
confidence: 96%
“…In one publication on the effects of sodium alginate on the respiratory exposure to raw seaweed dust, it has been reported that it causes pulmonary hypersensitivity, although it is not clear that pure sodium alginate would have the same effects (Henderson et al, 1984). However, considering that the product is a dermal sensitiser, the Panel concludes that sodium alginate should be considered also a respiratory sensitiser.…”
Section: Assessmentmentioning
confidence: 99%
“…No specific information on the safety of sodium and potassium alginate for the user was provided. From the available information, the only effect reported for alginate is a pulmonary hypersensitivity in an occupational context (Henderson et al, 1984). Given the high dusting potential and the high proportion of particles of respirable size, exposure via inhalation is regarded as hazardous.…”
Section: Safety For the Usermentioning
confidence: 99%